Gold Investment at Hajj Financial Management Agency (BPKH) - Damayanti, Mutia Melina; Busnetty, Ida; Amran, Ellyana; Ratnawati, Nirdukita; Soeharjoto (International Journal of Islamic Finance, 2024)
This research aims to analyze the influence of macroeconomic factors on price movements in Pegadaian gold accounts, analyze the factors that BPKH must put into consideration when investing in gold, and analyze the better gold instrument that are more recommended for BPKH between gold bullion and gold accounts. The influence of macroeconomic factors’ analysis on the price movement of Pegadaian gold accounts was carried out using a multiple linear regression method with five independent variables, namely international gold prices, inflation rate, rupiah exchange rate against USD, interest rate, economic growth rate, and one dependent variable, namely price Pegadaian gold account. Meanwhile, analysis of the factors that BPKH must pay attention to when investing in gold and gold instruments is carried out using the ANP (Analytic Network Process) qualitative method. Multiple linear regression analysis shows that the international gold price, exchange rate, inflation rate, and economic growth rate have a significant effect on the price of Pegadaian gold accounts. Meanwhile, the interest rate does not have a significant effect on the price of Pegadaian gold accounts. The variables of international gold prices and the Rupiah exchange rate against USD have a positive correlation, while the variables of inflation rate, reference interest rate and economic growth rate have a negative correlation with the price of Pegadaian gold accounts. The results of ANP data processing confirm the results of multiple linear regression analysis, stating that international gold prices, the Rupiah exchange rate against USD, and the inflation rate are the three main macroeconomic factors that influence gold price movements. The results of the ANP questionnaire processing also state that BPKH needs to pay attention to several factors in investing in gold, namely macroeconomic factors, risk factors and sharia compliance factors. As many as 90% of respondents to the ANP questionnaire recommended Pegadaian gold accounts as a better investment instrument for BPKH considering the mitigation of operational risk and is considered more liquid, referring to Pegadaian buyback policy. Meanwhile, 10% of respondents to the ANP questionnaire preferred gold bullion instruments with clearer sharia contract considerations. In order to diversify as well as to maintain asset value when unstable economic conditions occur, BPKH should increase the gold investment portfolio with maximum limit is 5% of the total investment and/or bank placement of hajj fund. When investing in gold, BPKH should pay attention to the movements in macroeconomic factors, namely international gold prices, exchange rates, inflation rate and economic growth rates. BPKH must also pay attention to risk factors and sharia comply of the gold instrument. Apart from the efforts to increase the financial benefits of hajj fund through optimizing gold investment, the percentage of cost paid by pilgrims also plays an important role in supporting the sustainability of hajj fund. In this case, the the percentage of cost paid by pilgrims should be adjusted rationally. Total hajj cost is also a crucial aspect, especially in the main components such as flight costs, hotels and catering. The efficiency of these components can be strived by collaborating with airlines or aviation fuel providers, purchasing hotels/ apartments in Mecca and/or Medina, and establishing catering factories for Indonesian hajj pilgrims. The initiation of these investment can be explored conjointly with the Ministry of Religion as the organizer of Indonesian Hajj pilgrimage.